A PERANCANGAN SISTEM INFORMASI BERBASIS WEB UNTUK PENYANDANG DISABILITAS PADA DINAS SOSIAL KOTA MEDAN: Mengembangkan sistem informasi berbasis web yang akan membantu Dinas Sosial Kota Medan mengelola data penyandang disabilitas secara efektif dan efisien - Ali Ikhwan; Fauzan Nafis; Aulia, Dhafa (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Persons with disabilities face difficulties in accessing the social services available to them, especially regarding data collection and information management. This research aims to develop a web-based information system that will assist the Medan City Social Service in effectively and efficiently managing disability data. This system is intended to make data recording, searching, and reporting easier, which will help improve the quality of services provided to the community. Needs analysis, system design, implementation, and testing are the methodologies used in this research. Web-based technology is used to develop this system, which includes programming languages and databases (e.g., PHP, Python, or others). Individual data management, data searching, and statistical report generation are the main features provided. The research results indicate that this information system has the capability to improve the accuracy of data collection and reduce the time needed to process data. With this system, the Social Service of Medan City can provide more organized services to meet the needs of people with disabilities.